2007
DOI: 10.17221/2000-vetmed
|View full text |Cite
|
Sign up to set email alerts
|

Intraspecific and interspecific chemosignals in birds: a review

Abstract: This review of chemosignals in birds considers intraspecific oriented chemosignals such as pheromones, interspecific chemosignals, and chemical interactions with parasites. Intraspecific chemosignals are known in some seabirds, especially burrow-or crevice-nesting auklets and petrels that breed in large colonies and are often nocturnal on land. Crested Auklets secrete a distinctive scent closely associated with courtship and important in sexual selection. Individually distinctive odours of petrels allow them t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…Located at the base of the tail, the gland is the source of a diverse mixture of organic compounds [14] that birds spread over their feathers during preening. In addition to waterproofing and conditioning the feathers [15], the secretions may also function in intraspecific and interspecific communication (see reviews [16,17]). The role of the gland in Cx.…”
Section: Introductionmentioning
confidence: 99%
“…Located at the base of the tail, the gland is the source of a diverse mixture of organic compounds [14] that birds spread over their feathers during preening. In addition to waterproofing and conditioning the feathers [15], the secretions may also function in intraspecific and interspecific communication (see reviews [16,17]). The role of the gland in Cx.…”
Section: Introductionmentioning
confidence: 99%
“…Nowadays, it has been shown that olfaction may be a more important sense in birds than was traditionally believed (Steiger et al 2008). Recent evidence suggests that birds can use odours in several ecological contexts and with different functions (Roper 1999, Hagelin 2007, Hagelin & Jones 2007, Rajchard 2007, 2008, Balthazart & Taziaux 2009, Caro & Balthazart 2010. At the intra-specific level, they are known to emit chemical compounds, which are important in several aspects of avian life histories (Caro & Balthazart 2010).…”
mentioning
confidence: 99%
“…Evidence of chemical deterrents of ectoparasites in birds is reduced to a handful of bird species, and it does not include uropygial secretions but compounds produced in the skin or feathers (reviewed by Dumbacher and Pruett-Jones, 1996;Moyer and Clayton, 2004;Rajchard, 2007Rajchard, , 2010Caro et al, 2015). Crested auklets (Aethia cristatella) emit a characteristic citrusy odor, which is associated from specialized wick feathers in the interscapular region.…”
Section: Discussionmentioning
confidence: 99%